Letter
1940-04-18 013-0090-001 FINNISH LEGATION LONDON. ABBEY 4741-2-3. No 8563 37, SMITH SQUARE, WESSTMINSTER, S.W.1. 18th April, 1940. Dear Madam Referring to your letter of the 27th March last, I write to inform you that I have now received definite information concerning the man named Gunnar Ebb, about whom you made enquiries. The actual name of the man in question is Paavo Koskinen, although he used, when in Spain, the name of Gunnar Ebb. Together with other volunteers from Spain, he returned to Helsinki on December 12th, 1938, and was remanded in custody because he had participated in illegal Communist activities in Finland during the years 1934 and 1935. The police had been already then looking for him, but found out that he had escaped to the U.S.S.R., from where he is believed to have gone to Spain. General Secretary, Sir Walter Citrine, K.B.E Transport House, Smith Square, S.W.1. 292/946/13/90(i)